Follow the Leader: Mimetic Isomorphism and Entry Into New Markets - Haveman, Heather A. (Administrative Science Quarterly, 1993)
Follow the Leader: Mimetic Isomorphism and Entry Into New Markets Heather A. Haveman Administrative Science Quarterly, Volume 38, Issue 4 (Dec., 1993), 593-627. Stable URL: http://links.j stor.org/sici?sici=OO01—8392%28199312%2938%3A4%3C593%3AFTLMIA%3E2.0.CO%3B2—V Your use of the JSTOR archive indicates your acceptance of J STOR’s Terms and Conditions of Use, available at http://www.jstor.org/about/terms.html. JSTOR’s Terms and Conditions of Use provides, in part, that unless you have obtained prior permission, you may not download an entire issue of a journal or multiple copies of articles, and you may use content in the JSTOR archive only for your personal, non—commercial use. Each copy of any part of a JSTOR transmission must contain the same copyright notice that appears on the screen or printed page of such transmission. Administrative Science Quarterly is published by Cornell University, Johnson Graduate School of Management. Please contact the publisher for further permissions regarding the use of this work. Publisher contact information may be obtained at http://www.jstor.org/joumals/cjohn.html. Administrative Science Quarterly ©1993 Cornell University, Johnson Graduate School of Management JSTOR and the JSTOR logo are trademarks of JSTOR, and are Registered in the U.S. Patent and Trademark Office. For more information on JSTOR contact jstor—info@umich.edu. ©2002 JSTOR http://www.j stor.org/ Mon Jan 21 17:34:52 2002